An annotated Checklist of some Orthopteroid insects of Mapimi Biosphere reserve (Chihuahuan desert), Mexico - Rivera García, Eduardo (Instituto de Ecología, A.C., 2006)
The Orthopteroidean fauna in Mapimi Biosphere Reserve (RBM) is represented by 60 species. Ensifera suborder are represented by 15 species grouped in next superfamilies: Tettigoniidae (8 species), Tettigonoidea (one), Stenopelmatoidea (one), Grylloidea (four) y Gryllotalpoidea (one), and six species recorded of Phasmatodea and Dyctioptera orders. In Caelifera suborder, grasshopper fauna is composed of 39 recognized species. The family Acrididae is represented by the subfamilies Gomphocerinae (13 spp), Oedipodinae (10 spp), Melanoplinae (9 spp), Cyrthacantacridinae (2 spp), Ommatolampinae (1 sp), Leptysminae (1 sp), and Romaleidae family (3 spp). Three major life-form groups or guilds are found at MBR: 1) Ground-dwelling species (terricoles), the most common of which are Trimerotropis pallidipennis (Burmeister 1883) and Cibolacris parviceps (Walker 1870). These species live on the soil surface, are generalist feeders and tend to specialize on specific soils associated with different geomorphic surfaces. 2) Grass-dwelling species (graminicoles), the most common being Paropomala virgata Brunner 1899, Opeia obscura (Thomas 1872), and frequent outbreaks of Boopedon nubilum (Say 1825). These species live and feed on grasses but have no specific hosts. 3) Shrub-dwelling species (arbusticoles), which are morphologically, behaviourally, and trophically distinct from ground-dwelling and grass-dwelling species. The most common are Bootettix argentatus Brunner 1889, Ligurotettix planum (Brunner 1905), Hesperotettix viridis (Thomas 1872), Campylacantha olivacea Scudder 1875, and Clematodes larreae Cockerell, 1901; shrub-dwelling species live and feed on shrubs and are host specific to particular shrub species. In general, the species composition and density of grasshopper assemblages vary with different landscape units (depending on soils type and conditions) and also depend on to the taxonomic and physical structure of vegetation and climate into MBR.